Early detection and treatment of obstructive sleep apnoea in infants with Down syndrome: a prospective, non-randomised, controlled, interventional studyResearch in context - Brigitte Fauroux; Silvia Sacco; Vincent Couloigner; Alessandro Amaddeo; Aimé Ravel; Emmanuelle Prioux; Jeanne Toulas; Cécile Cieuta-Walti; Hervé Walti; Romain Luscan; Ségolène Falquero; Manon Clert; et al. (Elsevier, 2024)
Summary: Background: Infants with Down syndrome (DS) are at high risk of obstructive sleep apnoea (OSA) which is associated with neurocognitive dysfunction and behaviour problems. The aim of our study was to evaluate the effect of early OSA treatment in infants with DS on neurocognitive development and behaviour. Methods: In this prospective, interventional, non-randomised study, 40 infants with DS underwent polysomnography (PSG) every 6 months in room air between 6 and 36 months of age (Screened Group) and were compared to a control group of 40 infants with DS receiving standard of care and a single, systematic PSG in room air at 36 months of age (Standard Care Group). When present, OSA was treated. The primary endpoint was the total score of the Griffiths Scales of Child Development, Third Edition (Griffiths III) and its subscores at 36 months. Secondary endpoints included a battery of neurocognitive and behaviour questionnaires, and PSG outcomes. Findings: On the Griffiths III, the total score was significantly higher in the Screened Group compared to the Standard Care Group (difference: 4.1; 95%CI: 1.3; 7.6; p = 0.009). Results in Griffiths III subscores and secondary endpoints were in support of better neurocognitive outcomes in the Screened Group compared with the Standard Care Group. At 36 months, median (Q1; Q3) apnoea-hypopnea index was higher in the Standard Care Group (4.0 [1.5; 9.0] events/hour) compared to the Screened Group (1.0 [1.0; 3.0] events/hour, p = 0.006). Moderate and severe OSA were more frequent in the Standard Care Group as compared to the Screened Group (18.9% versus 3.7% for moderate OSA and 27.0% versus 7.4% for severe OSA). Interpretation: Early diagnosis and treatment of OSA in infants with DS may contribute to a significantly better neurocognitive outcome and behaviour at the age of 36 months. Funding: The study was funded by the Jérôme Lejeune Foundation.